The Integration of Listening and Speaking to Develop Students’ Communicative Competence in Islamic Boarding School - L. M. Asy'ari Rahim; Budi Hermawan (ITScience (Information Technology and Science), 2024)
In real-life conversation, listening and speaking skills coexist and are not mutually conflicting. However, studies about the integration of listening and speaking in the classroom are still rare. Hence, this study aims to investigate how teachers integrate listening and speaking to develop students' communicative competence and the challenges teachers face during the English learning process. The study uses a qualitative case study with four English teachers. Data is collected through observations and interviews. The findings indicate that the teachers familiarize students with listening to various English audio daily since the students stay in a dormitory. In the classroom, the teachers often use conversation audio while the students are asked to follow along with the audio script. Then, two students are asked to come forward and practice with a partner. Students are also given tasks to create short conversations with their friends based on the themes learned from the audio played by the teachers. This integration of listening and speaking activities is expected to help students develop their communicative competence. Some challenges that often arise include students feeling embarrassed to practice in front of their peers and teachers paying less attention to students seated in the back, leading to disengagement during the audio sessions. However, this study suggests that teachers provide more control, motivation, and a sense of comfort for students to address these challenges.